Approximate State Transition Matrix and Secular Orbit Model. (10th March 2015) - Ramachandran, M. P.
Abstract : The state transition matrix (STM) is a part of the onboard orbit determination system. It is used to control the satellite's orbital motion to a predefined reference orbit. Firstly in this paper a simple orbit model that captures the secular behavior of the orbital motion in the presence of all perturbation forces is derived. Next, an approximate STM to match the secular effects in the orbit due to oblate earth effect and later in the presence of all perturbation forces is derived. Numerical experiments are provided for illustration.